Emerging Themes in Islamic Education and Social Media Research: A Scopus-Based Analysis - Amaliatul Fitriyah; Benny Prasetiya; Febry Suprapto; Khoiriyah Khoiriyah (Immortalis Journal of Interdisciplinary Studies, 2026)
The rapid development of social media and digital technologies has significantly influenced the field of Islamic education. The integration of social media into Islamic pedagogy has transformed traditional learning methods, fostering deeper student engagement and enhancing the delivery of Islamic values. This study explores the emerging trends in the relationship between Islamic education and social media through a bibliometric approach, analyzing publications indexed in Scopus from 2018 to 2023. The research aims to identify key themes, trends, and patterns of collaboration within this field, along with the potential future directions for research. Using a systematic literature review (SLR) approach guided by the PRISMA 2020 framework, the study investigates the growing role of social media in Islamic education, focusing on the integration of Islamic values, character development, and digital literacy. The results indicate that social media plays a central role in enhancing Islamic education by fostering a more inclusive and collaborative learning environment. The findings also highlight the increasing interdisciplinary nature of research in this field, with contributions from diverse academic disciplines. The study contributes to the growing body of knowledge by offering a comprehensive bibliometric analysis and network visualization that maps the development of research in this area, providing valuable insights for future academic and practical applications in the context of Islamic education and digital technology.